The first Hapalotremus Simon, 1903 (Araneae: Theraphosidae) from Argentina: description and natural history of Hapalotremus martinorum sp. nov. - Cavallo, Patricio (2014)
A new species of Hapalotremus Simon, 1903 from northern Argentina is described and illustrated. Hapalotremus martinorum sp. nov. differs from all other congeners by the colour pattern of live specimens. Males differ in the male palpal bulb morphology, with thickened and less curved embolus having a blunt subapical keel and less-developed apical keel. Females differ in the shape of the spermathecae, with the lateral bases more pronounced than the superiors and the upper edge more rounded. Specimens were captured inhabiting short burrows or crevices under stones in high cloud forests. Hapalotremus cyclothorax (Mello-Leitão 1923) is a junior synonym of Homoeomma montanum (Mello-Leitão, 1923), Hapalotremus scintillans (Mello-Leitão 1929) is a junior synonym of Pachistopelma rufonigrum Pocock, 1901, Hapalotremus exilis (Mello-Leitão 1923) and Hapalotremus muticus (Mello-Leitão 1923) are considered species inquirenda.